Effectiveness of Cherry Tomato Extract in Gel Form to Accelerate the Healing Process of Excision Wounds in Wistar White Rats - Fertilita, Soilia; Zulfadli, Muhammad; Larasati, Veny; Rasyid, Riana Sari Puspita; Argentina, Fifa; Tanta, Yudhi; Athiah, Medina (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Cherry tomatoes (Solanum lycopersicum L. var. cerasiforme) are rich in antioxidants, particularly flavonoids and lycopene, which help reduce free radicals and promote wound healing. Flavonoids exhibit anti-inflammatory, antioxidant, antibacterial, and antidiabetic properties. They enhance wound contraction, collagen deposition, granulation tissue formation, and epithelialization in wound healing. This study evaluates the efficacy of cherry tomato extract gel in accelerating excision wound healing in Wistar rats. This in vivo experimental study used a post-test control group design. Twenty-five 2–3-month-old Wistar rats with excision wounds were treated with cherry tomato extract gel or controls. The five groups included a positive control (NaCl), a negative control (CMC-Na gel), and treatment groups receiving 8%, 12%, or 16% extract gel. Wound size was measured on days 3, 5, 7, and 9, with data analyzed using One-Way ANOVA and post hoc tests. The extract-treated groups exhibited nearly complete wound closure by day 9. The wound size of the treatment groups significantly differed from the control groups (p<0.05). Cherry tomato extract gel significantly accelerates wound closure at 8%, 12%, and 16% concentrations, with the best results observed at 16% (p<0.05), surpassing even the positive control. The 16% extract gel group demonstrated the most effective wound healing. Cherry tomato extract gel significantly enhances wound healing, with the 16% concentration demonstrating the most effective acceleration of wound closure. These findings suggest that cherry tomato extract gel, particularly at 16%, holds promise as a potent wound-healing agent.